KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL OPEN-ENDED MATERI DIMENSI TIGA DI SMK - Dahlila Handayani; Agung Hartoyo; Romal Ijuddin (Universitas Tanjungpura, 2019)
AbstractThis research aimed to explore student’s creative thinking ability in solving open ended problems on three dimensional material of SMK Negeri 3 Pontianak. The research method used in this study in the mixed method (quantitative and qualitative) with type triangulation design. The techniques used were measurement techniques and direct communication techniques with data collection tools creative thinking ability test and interview guide. The subject of this research was 40 students of XI AP3 SMK Negeri 3 Pontianak. The result showed that there were 6 (15%) students with the most creative thinking level, 14 (35%) students with creative thinking level, 2 (5%) students with moderate creative thinking level, 9 (22,5%) students with less creative thinking level, and 9 (22,5%) students with not creative thinking level. In fluency aspect of creative thinking, there were 30 (75%) students qualified and 10 (25%) students satisfied. In flexibility aspect of creative thinking, there were 20(50%) students qualified and 20 (50%) students satisfied. In originality aspect of creative thinking, there were were 8 (20%) students qualified and 32 (80%) students satisfied.Keywords: Creative Thingking, Open Ended Problem, Three Dimensional Material